Typifications of five names in Agarista (Ericaceae, Vaccinioideae, Lyonieae) - Dalastra, Claudenice Hilda; Heiden, Gustavo (Phytotaxa, 2020)
Five names are typified here as a first step towards the floristic and taxonomic study of Ericaceae in Rio Grande do Sul state, Brazil, and the taxonomic revision of Agarista. We reviewed protologues, type specimens (including digital images), and negative photos at F from lost specimens originally deposited at B. Lectotypes are designated for the names Andromeda chlorantha, A. serrulata, A. eucalyptoides, A. multiflora, and A. nummularia. These lectotypes are designated from duplicates conserved in the herbaria E, F, HAL, G, GH, L, M, NY, S, and W. Additionally, epitypes are also designated for Agarista chlorantha and Agarista nummularia at ESA and US, respectively.